ANALISIS PENGARUH INVESTASI TERHADAP HUTANG PADA PERUSAHAAN MANUFAKTUR YANG LISTED DI BURSA EFEK JAKARTA - Tripitono Adi Prabowo (MediaTrend, 2006)
This research tested the prediction of effect the investment of the financial leverage in manufacture companies listed on Jakarta Stock Exchange. Variable used in this research is financial leverage (Y), dividend payout ratio (X1), investment (X2), Firm's risk (X3), asset structure (X4), and firm's size (X5). Analysis tool used to test those above is regression least squares program for windows. This research use manufacturing companies listed on Jakarta Stock Exchange as samples, with period of observation from 1992 to 1995, resulting 159 companies. This research result that investment doesn't effect on financial leverage significantly.